Salicylic acid derivatives as potential α-glucosidase inhibitors: drug design, molecular docking and pharmacokinetic studies - Khalifa Sunusi Aminu; Adamu Uzairu; Abdullahi Bello Umar; Muhammad Tukur Ibrahim (Bulletin of the National Research Centre, 2022)
Abstract Background Diabetes mellitus (DM) is one of the most defying health risk in the twenty-first century promoting a high rate of morbidity and mortality that could possibly increase if no intervention is in place. However, drugs for curing DM are available but are associated with adverse side effect necessitating the pursuit for a safe antidiabetic drugs. The present study was conducted in order to develop a QSAR model that would be used to predict the activities of salicylic acid derivatives, as well as to determine the binding interactions of the compounds with α-glucosidase using molecular docking studies. Results Model one was selected and reported as the best model based on its fitness with the following validation keys: R 2 (trng set) = 0.968, R 2 (adj) = 0.957, Q 2 (cv) = 0.932, LOF = 0.085 and R 2 (test set) = 0.864. Five potent analogues were designed using the ligand-based method with their predicted activities been calculated and found to be higher compared to the lead compound. Furthermore, binding interactions of the designed analogues within the active site of α-glucosidase (pdb id:3L4V) illustrate a good binding affinities than kotalanol and acarbose. However, the ADMET and drug-likeness properties predicted the design analogues to be pharmacologically and orally safe by not having more than one violation of Lipinski’s (Ro5) criteria. Conclusions The present findings therefore showed that the salicylic acid derivatives could serve as α-glucosidase inhibitors. The compounds can be studied further for a hunts of promising drug candidates against diabetes mellitus.